Marketing of Hybrid Corn in Tapenpah Village, Insana District, North Central Timor Regency during the New Habit Adaptation Period - Kanisius Siki; Umbu Joka; Agustinus Nubatonis (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2021)
The goal of this study was to determine the general definition of the marketing channel, to know the marketing roles, the marketing margins, and to use a marketing analysis to determine the price earned by hybrid corn traders. The sampling scheme was carried out by purposive sampling on hybrid corn dealers, the number of samples taken by as many as 26 respondents. The data collection tool was used to perform interviews with respondents using questionnaires. The methodological method used was the study of the marketing margin. The findings showed that the margin at the retailer level was IDR 500/kg (0.11 percent) while the retailer margin was IDR 1500/kg (0.11 percent) (0.25 percent). This means that the difference between the purchasing price and the sale price of the collector is less than the difference between the purchase price and the retail price. Since there are two elements in the marketing margin, namely the expense component and the benefit component.  Thus, the price component is IDR 4.500/kg (0.11 percent) and IDR 6.000/kg (0.25 percent) for retailers. This indicates that the market prices by the collectors are higher than the retailers